The Conundrum of Genetic "Drivers" in Benign Conditions - Kato, Shumei; Lippman, Scott M; Flaherty, Keith T; Kurzrock, Razelle (JNCI : Journal of the National Cancer Institute, 2016)
Advances in deep genomic sequencing have identified a spectrum of cancer-specific passenger and driver aberrations. Clones with driver anomalies are believed to be positively selected during carcinogenesis. Accumulating evidence, however, shows that genomic alterations, such as those inBRAF,RAS,EGFR,HER2,FGFR3,PIK3CA,TP53,CDKN2A, andNF1/2, all of which are considered hallmark drivers of specific cancers, can also be identified in benign and premalignant conditions, occasionally at frequencies higher than in their malignant counterparts. Targeting these genomic drivers can produce dramatic responses in advanced cancer, but the effects on their benign counterparts are less clear. This benign-malignant phenomenon is well illustrated in studies ofBRAFV600E mutations, which are paradoxically more frequent in benign nevi (∼80%) than in dysplastic nevi (∼60%) or melanoma (∼40%-45%). Similarly, human epidermal growth factor receptor 2 is more commonly overexpressed in ductal carcinoma in situ (∼27%-56%) when compared with invasive breast cancer (∼11%-20%).FGFR3mutations in bladder cancer also decrease with tumor grade (low-grade tumors, ∼61%; high-grade, ∼11%). "Driver" mutations also occur in nonmalignant settings:TP53mutations in synovial tissue from rheumatoid arthritis andFGFR3mutations in seborrheic keratosis. The latter observations suggest that the oncogenicity of these alterations may be tissue context-dependent. The conversion of benign conditions to premalignant disease may involve other genetic events and/or epigenetic reprogramming. Putative driver mutations can also be germline and associated with increased cancer risk (eg, germlineRASorTP53alterations), but germlineFGFR3orNF2abnormalities do not predispose to malignancy. We discuss the enigma of genetic "drivers" in benign and premalignant conditions and the implications for prevention strategies and theories of tumorigenesis.